Fully corrected estimates of common minke whale abundance in West Greenland in 2007 - Heide-Jørgensen, M. P.; Witting, L.; Laidre, K. L.; Hansen , R. G.; Rasmussen , M. (J. Cetacean Res. Manage., 2023)
A visual aerial line transect survey for common minke whales (Balaenoptera acutorostrata) was conducted off West Greenland in August and September 2007. A total of 8,670km of survey effort covered 11 strata in sea states <5 with a total stratum area of 213,807km2 . The 27 sightings of common minke whales were all within a strip width of 300m and the average time from first detection to when the sighting passed abeam was 1.7 sec. Due to the uniform and narrow distribution of the detections, strip census methods were used to analyse the survey. Two methods were deployed to correct the strip census estimates for whales missed by the observers and whales that were submerged during the passage of the plane. Method 1 included all detections of common minke whales (n = 27) and correction for an instantaneous availability that included submergence of whales. Using data from sea states <3 (n = 22) the ‘at surface’ abundance of common minke whales was 1,866 (CV = 0.30) whales. A correction for whales missed by the observers with a simple mark-recapture estimator resulted in a corrected abundance of 1,904 (CV = 0.30) whales. Adjusting for the availability bias resulted in a fully corrected estimate of 16,609 (95% CI 7,172–38,461) common minke whales. Method 2 used only detections of common minke whales that were observed to break the surface (n = 19). Applying this method to effort data at sea state <3 (n = 14) resulted in an ‘at surface’ abundance of 1,174 (CV = 0.39) whales. A correction for whales missed by the observers increased the abundance to 1,198 (0.39) whales. Adjusting for the availability bias resulted in a fully corrected estimate of 22,952 (95% CI 7,815–67,403) common minke whales.